The Influence of Training and Education on Human Resource Development with the Support of Facilities and Infrastructure as a Moderating Variable at PT Energi Persada Inti Kontruksi Jakarta - Muhammad Irfan Akbar; Sri Rahayu; Kiki Farida Ferine (CV. Doki Course and Training, 2026)
Human resource development (HR) is essential to ensure the long-term progress of the organization and maintain competitiveness, especially in the construction sector where continuous upskilling and adaptability are essential. This study seeks to empirically examine how training and education affect human resources, with infrastructure facilities acting as a moderation factor. This study was conducted at PT Energi Persada Inti Kontruksi Jakarta using a quantitative method through a structured survey involving 126 employees. Data were processed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate the immediate effects and moderation. The results of the study show that training and education each have a positive and significant influence on human resources. In addition, infrastructure facilities substantially strengthen the effects of training and education on human resource outcomes. These findings emphasize the strategic value of integrating strong training and education initiatives with adequate infrastructure support to improve employee capabilities and overall organizational effectiveness. This study enriches the human resource literature by describing the role of infrastructure moderation in the industrial environment and provides practical insights for managers in improving learning environments and capacity building efforts.